The Coalition Crumbles, Napoleon Returns : The 1799 Campaign in Italy and Switzerland, Volume 2 - Clausewitz, Carl von, 1780-1831 (Book collections on Project MUSE., 2021)
"The writings of Carl von Clausewitz (1780-1831) are among the most important works on war ever written. Much of the focus has understandably been on his great theoretical work On War, published in 1832. That work, however, formed only the first three of the ten volumes of his published writings. For Napoleon Absent, Coalition Ascendant, Murray and Pringle have chosen the original version of the text published in 1833 which is the first of the two volumes originally published as Der Feldzug von 1799 in Italien und der Schweiz. In these two volumes, Clausewitz describes and analyses the campaigns of 1799 in Italy and Switzerland, providing a superb history of this episode of the French Revolutionary wars. He covers the campaigns in detail and provides excellent analysis of their events, along with what he identifies as the changes in warfare that rocked Europe from 1792-1815. These campaigns were an important part of the wars of the French Revolution and Napoleonic period, but they have never been covered adequately from a historical standpoint."--